The Sex Radicals Free Love in High Victorian America - Sears, Hal D. (University Press of Kansas, 1977)
This volume provides the first account of the pioneering efforts at sex reform in America from the Gilded Age to the Progressive era. Despite the atmosphere of extreme prudery and the existence of the Comstock laws after the Civil War, a group of radicals emerged to attack conventional beliefs about sex, from traditional marriage to women's chattel status in society. These men and women had in common a direct, unrespectable, iconoclastic style. They put forth outrageous journalism and had a penchant for martyrdom and for using the courts to publicize their ideologies.From rare and generally unknown sources, Hal D. Sears pieced together the story of the sex radicals and their surprising ideas. Moses Harman, a minister turned abolitionist and freethinker, is a central figure in the narrative. His Lucifer, the Light Bearer, the only journal of sexual liberty published from the early 1880s to 1907, was dedicated to free love, sex education, women's rights, and related causes. To a great degree Harman's publication defines the limits of social dissent in the late nineteenth century.Other members of the sex radical circle included E. B. Foote, a medical doctor who made a fortune with a home medical book crammed with sex information; Edwin Walker and Lillian Harman, who became a cause célèbre among radicals when their jailhouse honeymoon in Kansas challenged the right of the state to regulate marriage; Elmina Slenker, who promoted a theory of sexual energy sublimation and the idea that women were the superior sex; and Lois Waisbrooker, Dora Forster, Lillie White, and other feminists who, almost a century ago, taught and preached the very ideas we hear today in the women's movement.Of course, all these people got into trouble with the law, mostly through the machinations of their archvillain, Anthony Comstock. Sears examines Comstock's powers of postal censorship and describes Comstock's personal vendettas against sexual dissenters, particularly the free love philosopher Ezra Heywood. He gives a legal history of obscenity and explains the sex radicals' significance in the emergence of obscenity law.Although the sex radicals attest the important reform vitality of provincial culture in late nineteenthcentury America, until now they have been almost ignored by historians. Those who have studied sex radicalism at all, apart from its communitarian and sectarian aspects, have viewed it merely as a subsidiary of the more respectable feminist movement. In this book Sears gives careful consideration to the links between sex radicalism and spiritualism, feminism, anticlericalism, anarchism, and the freethought movement. He presents sex radicalism as a separate and unique movement which illuminates new reaches of the Victorian landscape and establishes a tradition for presentday liberation trends.